Paul: Jew, Greek, and Roman - Porter, Stanley E., 1956- (Pauline Studies, 2008)
What does it mean to study Paul the Apostle as Jew, Greek, and Roman? The framing of the question exposes the fact that the distinctions themselves involve a complex of ethnic, social, and cultural designations. Paul is both a complicated individual of the ancient world, because he combines in his one personage features of life in each of these cultural-ethnic (and even religious) areas of the ancient world, and one of many people of that world who evidenced such complexity. This volume, Paul: Jew, Greek, and Roman, explores a number of the important and diverse cultural, ethnic, and religious dimensions of the multi-faceted background of Paul the Apostle. Some of the treatments are focused and specific, while others range over the broad issues that go to making up the world of the Apostle.